ОСОБЛИВОСТІ РОЗВИТКУ КОРПОРАТИВНОЇ СОЦІАЛЬНОЇ ВІДПОВІДАЛЬНОСТІ ПІДПРИЄМСТВ - Kachan, I.V.; Shelest, O.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper studies the evolution of approaches to corporate social responsibility understanding both in the world and Ukraine. Basic conceptions of corporate social responsibility are considered in a general view. The distinctive features of the Ukrainian model of corporate social responsibility are grounded.